MUATAN PORNOGRAFI ANAK PADA LINGKARAN PEDOFILIA DI DUNIA MAYA - Yogatama, Astri (Scriptura, 2009)
Child exploitation by online paedophile is all over the world. Image, chat and audio-visual child pornography is exchange in the ring of online paedophile. Certain countries have developed strong cyberlaw to attack the presence of this dangerous cyber communities. Cyber Law still needs precise definition of child pornography content, specially in cyberworld. The definition must cover image, chat, audiovisual, writing of a child, in the sexual conduct and pseudo-pothograph.